Strategi Peningkatan Fasilitas Perpustakaan di Universitas Singaperbangsa Karawang - Aulia Siti Aminah; Putri Ainun Nisa; Bintang Taufik Alfarizy; Hinggil Permana (STAI AL-AMIN, 2025)
This research aims to explore strategies for improving library facilities at Singaperbangsa Karawang University in an effort to enhance the quality of education and literacy in the academic environment. The research method used is descriptive qualitative, with data collection through observation, interviews, and documentation. The research results indicate that five main strategies can be used to improve library facilities: first, enhancing the collection of books and digital resources; second, improving the infrastructure of reading facilities; third, developing training and human resources; fourth, collaborating with external parties; and fifth, developing digital-based library services. The development of digital collections, such as e-books and electronic journals, and collaboration with publishers and other institutions, is crucial for improving access to information. But the main challenges remain the limitations of space and funding. To increase the utilization of digital services, librarians and users must be trained. To become an inclusive, innovative library that meets the needs of the academic community, this research found that the Singaperbangsa Karawang University library needs to strengthen its digital infrastructure, enhance collaboration with professional networks, and optimize human resource training. The library can function as an effective learning center and support the academic and research goals of the university.